OBSERVING THE INFLUENCE OF MINDFULNESS AND ATTACHMENT STYLES THROUGH MOTHER AND INFANT INTERACTION: A LONGITUDINAL STUDY. Issue 3 (3rd May 2017) - Pickard, Judy A.; Townsend, Michelle; Caputi, Peter; Grenyer, Brin F. S.
ABSTRACT: The cross‐generational influence of attachment security or insecurity on caregiving is well‐established. Recently, research has focused on mindfulness as a potential variable to interrupt the transmission of insecure attachment and disrupt its effect across generations. Thirty‐six pregnant female participants completed the Five Facets Mindfulness Questionnaire and Relationship Questionnaire‐Clinical Version at 30 weeks' gestation. Following the infant's birth, mothers and their babies participated in a video‐recorded feeding session at 7 to 10 weeks' postpartum. It was predicted that a secure attachment style and higher levels of mindfulness measured prenatally would be associated with greater maternal responsiveness postpartum. The hypothesis was supported for both the secure and insecure (fearful and profoundly distrustful) attachment styles. Mindfulness did not mediate the relationship between attachment and maternal distress. The mindfulness subscale Non‐Reacting was significantly associated with maternal response to distress. These findings support the role of prenatal mindfulness skills and attachment security for later postnatal maternal sensitivity to baby.